Assessment of E. coli and E. coli O157:H7 Contamination in Cattle Carcasses, Workers, Equipment and Contact Surfaces of Unguwa-uku Abattoir, Kano State, Nigeria - Sulaiman, Tasiu; Adamu, M. T.; Garba, L.; Tawfiq, Umar A.; Bukar, A.; Namadina, M. M.; Aminu, M. A.; Sani, H. (Sahel Journal of Life Sciences FUDMA, 2025)
Unguwa-Uku abattoir is one of the major meat suppliers in Kano city and environs. Despite its capacity and importance in meat production and processing, most of the procedures are conducted under poor hygienic conditions, which may render the environment a potential source of pathogenic microorganisms. This study investigated the prevalence and distribution of Escherichia coli and E. coli O157:H7 in slaughtered cattle and environmental samples at the Unguwa-Uku abattoir, Kano State, Nigeria. A total of 80 samples, including carcass swabs, caecal contents, and contact surfaces, were collected and analysed using standard microbiological and biochemical methods, such as Indole, methyl red, Voges Proskauer and citrate tests. Results showed that 25% of the samples were positive for E. coli, while E. coli O157:H7 was detected in 8.75% of samples. The highest contamination was observed in caecal contents and cutting boards. Although E. coli O157:H7 was detected across multiple sample types, the association between sample type and prevalence was not statistically significant (P = 0.482). These findings highlighted potential hygiene risks in the abattoir environment and underscore the need for improved slaughterhouse sanitation and food safety practices.